Jorge Graciarena, na Perspectiva Latino-Americana: notas in memoriam - Ansaldi, Waldo; Giordano, Verónica (Departamento de Estudos Latino-Americanos - ELA, 2018)
In March 2014 Jorge Gracirena died, who was one of the founding figures of Argentine and Latin American sociology. However, the references to its vast production appear only sporadically in the programs of sociology courses nowadays. In these brief notes we address three aspects: the originality of his thought, beyond “scientific” sociology; his concern for postgraduate studies as a prism from which to capture this originality in the act; attention to the historical dimension of reality. The latter, as a presentation of the text “The Latin American State in Perspective. Figures, Crises and Prospects”, originally published in Madrid in 1984.